RESTORATION OF SEED FERTILITY IN ORDER TO RENEW THE SAMPLES OF VEGETABLE CROPS STORED IN THE GENE POOL - Alikulov Safar Menglikulovich; Buriev Khasan Chutbaevich; Abdullaev Faizulla Habibullaevich; Zokirov Kurbonalijon Gaybullo ogli (Journals Park Publishing, 2022)
The article presents the results of the research carried out in order to update the samples of the tomato, eggplant, hot pepper, sweet pepper collection from the vegetable crops stored in the gene pool and restore seed fertility.
Keywords: gene pool, crop samples, seed fertility, genetic resources, population